2008
DOI: 10.1124/mi.8.4.9
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Cancer Stem Cells with Phytochemicals

Abstract: Cancer, second only to heart disease, is the leading cause of death in the US. Although progress has been made in the early detection of cancer and in improvements of cancer therapies, the ability to provide long-term survival has been limited. Increasing evidence suggests that a minute, biologically unique population of cancer stem cells (SCs) exists in most neoplasms and may be responsible for tumor initiation, progression, metastasis, and relapse. Characterization of cancer SCs has led to the identification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
101
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(109 citation statements)
references
References 100 publications
0
101
0
2
Order By: Relevance
“…Therefore, Notch1 plays a pivotal role in tumorigenesis, selfrenewal and maintenance of side population cells in addition to stem cell maintenance and differentiation during embryonic and adult development (Artavanis et al, 1999;Lino et al, 2010). Similar to Notch1, it was shown that Hedgehog (Hh) and Wnt, are the other key factors involved in the regulation of self-renewal of cancer stem cells in different cancers (Kawasaki et al, 2008). Most likely, all these pathways collectively elevated and function together in side population cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, Notch1 plays a pivotal role in tumorigenesis, selfrenewal and maintenance of side population cells in addition to stem cell maintenance and differentiation during embryonic and adult development (Artavanis et al, 1999;Lino et al, 2010). Similar to Notch1, it was shown that Hedgehog (Hh) and Wnt, are the other key factors involved in the regulation of self-renewal of cancer stem cells in different cancers (Kawasaki et al, 2008). Most likely, all these pathways collectively elevated and function together in side population cells.…”
Section: Discussionmentioning
confidence: 99%
“…These cancer stem cells play a major role in tumorigenesis and also responsible for resistance to cancer therapies and tumor recurrence (Kawasaki et al, 2008). Several studies showed that cancer stem cells are highly self-renewal, possess differentiation potential, express stem cell surface proteins (e.g., CD24, CD44 and CD133), chemo-and apoptosis resistance.…”
mentioning
confidence: 99%
“…Work from our lab has identified that extracts of Tinospora cordifolia plant, used in many Ayurvedic preparations, is very effective against the drug resistant and stemness enriched side population cells of a variety of epithelial cancers [90]. Similarly, many other phytochemicals targeting CSCs have been identified and have reached stage II of clinical trials [91].…”
Section: Cscs and Microenvironmentmentioning
confidence: 99%
“…It has been estimated that nearly one third of all cancer deaths can be prevented by changing lifestyle and nutrition [16] and as dietary phytochemicals which are plant derived non nutritive compounds are well documented for their pleiotropic actions in suppressing tumor initiation and growth in a variety of cancers including leukemia, prostrate, breast, brain, melanoma and pancreatic [17] can act as promising anti cancer stem cell agents as they are well tolerated by the human system and can target the Wnt, Hedgehog and Notch embryonic pathways and tackle the problem of multi drug resistance. [2,18]. Signaling between two adjacent cells occur via binding of notch and delta which regulate cell fate decision.…”
Section: Introductionmentioning
confidence: 99%
“…The cytoplasmic tail of a single pass transmembrane protein notch is cleaved by γ-secretase complex when its extracellular domain binds to the ligand delta attached to an adjacent cell. The cytoplasmic tail called Notch Intracellular Domain (NICD) translocates to the nucleus and activates notch responsive genes which regulate renewal and pattern formation of tissues [2,18].…”
Section: Introductionmentioning
confidence: 99%